Developing a culture-based Indonesian language textbook for non-native speakers for academic purposes - Syamsi, Kastam; Zuchdi, Darmiyati; Kusmiatun, Ari; Purbani, Widyastuti; Masae, Aleeyah (Jurnal Cakrawala Pendidikan, 2024)
Language and culture could not be learned and taught separately. Therefore, a learning material based on culture should be considered for a meaningful instructional process. This study is aimed to develop a culture based textbook for academic purpose using a model of teaching language and culture. This model includes language  knowledge, language  awareness,  culture  awareness,  and  culture  experience. The first step (need assessment) concerning the need to develop a culture based textbook was done in the previous study by Zuchdi and Nurhadi (2019), while the level of students language competence and their cultural interest was done in the beginning of this study. This study was the development of an intercultural based textbook through these following procedures: defining objectives, identifying culture topics, developing materials and media of instruction, content layout and graphic design, internal and external review, try out for product validation, and developing final draft. Based on the survey, the majority of respondents were in level 3 and 4  of  Indonesian  language  competence,  so  this  textbook  was developed for that levels. The respondents were students taking Indonesian language program in Ahmad Dahlan University in Yogyakarta. The data were collected using pretest-postest and instructor's reflection, and then analyzed by finding out the difference between the scores category. Almost half of the pretest scores were in the low and medium category, while all of the postest scores were in the high category. Based on the the instructor's reflection, the students were really involving to study using this textbook. It can be concluded that the culture based Indonesian language textbook for academic purpose is effective for teaching and learning Indonesian as a foreign language.